Statistical Modelling of Integrated Security System - Eidukas, D.; Valinevičius, A.; Žilys, M.; Zavackis, D. (Elektronika ir Elektrotechnika, 2003)
Integrated security systems (ISS) are used most frequently at present. An ISS is the whole of technical tools created for transferringof alarm and service information as well as remote control commands to the central security station through communication channels.Aiming to decrease losses within the system, it is necessary to model an optimal number of communication channels within the securitysystem and algorithms for selection of a communication channel, which could increase effectiveness and reliability of the system. Inorder to be able to perform modeling of the optimal number of the security system’s connection channels as well as algorithms forselection of connection channels which would increase effectiveness and reliability of the system, we have used the “Arena” softwarepackage, by creating in its elemental base a digital model of the integrated security system without the influence of interferingparameters of the communication channels. Research has been made using streams of real security systems, which emerge out of the300 different purpose and different distribution objects of Kaunas city. The modeling results enable us to define the maximum permittedevent streams, where delay of registration of alarm and service events changes insignificantly. More significant increase in registrationdelays, when the streams are more intense, may be a cause of non-reliable work of the security system. Ill. 9, bibl. 2 (in Lithuanian;summaries in Lithuanian, English and Russian).